2016
DOI: 10.1111/btp.12319
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter decomposition rates in degraded and fragmented tropical rain forests of Borneo

Abstract: Previously extensive tracts of primary rain forest have been degraded by human activities, and we examined how the effects of forest disturbance arising from habitat fragmentation and commercial selective logging affected ecosystem functioning in these habitats by studying leaf litter decomposition rates in litter bags placed on the forest floor. The rain forests of Borneo are dominated by trees from the family Dipterocarpaceae, and we compared leaf litter decomposition rates of three dipterocarp species at ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Our study shows that a major driver of litter decomposition was land-use change and that substantial differences in litter quality associated with selectively logged and old-growth forest had no significant effect. We also discovered faster decomposition rates in undisturbed forest compared to selectively logged forest, which supports both our first hypothesis and previous work in a similar system (Yeong, Reynolds, & Hill, 2016). In general, decomposition was slow compared to other studies in tropical forests (Hättenschwiler, Coq, Barantal, & Handa, 2011;Powers et al, 2009) but comparable to mass loss reported by Mayor and Henkel (2006).…”
Section: Discussionsupporting
confidence: 90%
“…Our study shows that a major driver of litter decomposition was land-use change and that substantial differences in litter quality associated with selectively logged and old-growth forest had no significant effect. We also discovered faster decomposition rates in undisturbed forest compared to selectively logged forest, which supports both our first hypothesis and previous work in a similar system (Yeong, Reynolds, & Hill, 2016). In general, decomposition was slow compared to other studies in tropical forests (Hättenschwiler, Coq, Barantal, & Handa, 2011;Powers et al, 2009) but comparable to mass loss reported by Mayor and Henkel (2006).…”
Section: Discussionsupporting
confidence: 90%
“…This is contrary to expectations from previous studies (Ball, Lindenmayer, & Possingham, ; Blakely & Didham, ). However, high volumes of deadwood could be maintained in logged forest by lower decomposition rates (Ewers et al., ; Yeong, Reynolds, & Hill, ; but see Hérault et al., ), and large remnant pieces from harvest operations. In undisturbed forests, tree holes tend to be associated with larger, older trees (Blakely & Didham, ; Lindenmayer, Cunningham, Pope, Gibbons, & Donnelly, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to expectations from previous studies (Ball, Lindenmayer, & Possingham, 1999;Blakely & Didham, 2008). However, high volumes of deadwood could be maintained in logged forest by lower decomposition rates Yeong, Reynolds, & Hill, 2016; (Edwards, Tobias et al, 2014), increased wind in gaps (Chen, Franklin, & Spies, 1995) and remnant large trees that were specifically avoided by logging companies because of hollow boles. In addition, we assessed tree holes in the understorey only, and differences may well manifest at higher forest strata.…”
Section: Microclimate Availabilitymentioning
confidence: 99%
“…The research showing this is scanty, but there is evidence that decomposition rates are slower in disturbed (Didham ) and logged forest fragments (Yeong et al . ) compared with old growth forest. Furthermore, dead wood is proportionally more important for carbon storage in logged forest areas than in old growth areas (Pfeifer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Longer deadwood residence times may mean that there is more unsuitable wood for termites and fungi, but also more suitable wood for generalist ants, which could lead to indirect competition for dead wood. The research showing this is scanty, but there is evidence that decomposition rates are slower in disturbed (Didham 1998) and logged forest fragments (Yeong et al 2016) compared with old growth forest. Furthermore, dead wood is proportionally more important for carbon storage in logged forest areas than in old growth areas (Pfeifer et al 2015).…”
Section: Discussionmentioning
confidence: 99%